Waste heat recovery from exhausted gas of a proton exchange membrane fuel cell to produce hydrogen using thermoelectric generator. (15th March 2023) - Lan, Yuncheng; Lu, Junhui; Mu, Lianbo; Wang, Suilin; Zhai, Huixing
Highlight: The novel system consisting of a PEMFC, the TEG modules and a water electrolysis cell is proposed. The output power characteristics of wet exhausted gas from PEMFC are investigated. The economic and life cycle climate performance (LCCP) model are established to evaluate economic and environmental performance of system. Abstract: Proton exchange membrane fuel cell (PEMFC) is an efficient (40–50%) carrier to utilize hydrogen, which means around 50–60% of waste heat dissipates into ambience. To recover waste heat, advance hydrogen production and system efficiency, a novel integrated system with power generation and hydrogen production is proposed in this paper. The system includes a PEMFC, the thermoelectric generator (TEG) modules and a water electrolysis cell. The effects of cooling-method, electrical array configuration, the outlet temperature of PEMFC on the output power, system efficiency, hydrogen production rate and payback period have been investigated by means of a sensitivity analysis. The life cycle climate performance method is applied to evaluate the environmental performance. The results show that the hydrogen production rate of the water-cooling method is 31.4–44.8% larger than that of the air-cooling method. The electrical array configuration has no obvious effect on system performance. Additionally, the outlet temperature of PEMFC has positive effect on hydrogen production per module, while TEG module number is opposed. Furthermore, for optimizing the system, six different objection functions have been developed and compared. After optimization, the optimal height, area and volume of the thermoelectric leg are 1.01–1.3 mm, 2.52–3.28 mm 2 and 3.08–4.26 mm 3 at range of outlet temperature within 50–100 °C. The net output power, system efficiency and hydrogen production are 31.8–39.4%, 3.7–31.5% and 22.1–34.5% higher than that of the commercial module. The payback period and the year achieving zero carbon emissions are 15.0–34.3% and 17.8–36.8% lower than that of commercial module.